Moyshe Levin (Ber Sarin) of Yung-Vilne and His Solo Publishing Venture for Children - Berger, Shulamith (Judaica Librarianship, 2017)
Moshe [Moyshe] Levin, talented author and artist, was better known by his pseudonym Ber Sarin, the pen name he used when he wrote short Yiddish books in rhyme for children who were just beginning to read. He wrote the lively texts, illustrated them in color and black and white, and self-published many of them in Vilnius (Vilna) Lithuania in the 1930s. The books were popular and successful with teachers and children. He was a graduate of the Vladimir Medem Teachers’ Seminary, a teacher in the TSYSHO school system, and a member of Yung-Vilne .2017 is the 75th anniversary of Levin’s murder at the hands of the Nazis. Levin left behind a wife and daughter who also perished during the Holocaust. Levin’s literary legacy, the books themselves, survived in limited numbers in only a handful of libraries; some are now available on the web. This article includes a brief biography of Moshe ]Moyshe] Levin (Ber Sarin), an overview and discussion of his work for children, information on the current whereabouts of his works, and a bibliography with brief annotations of the works the author was able to view.